The predictive role of color doppler sonography in evaluating hypoxia and acidosis in intrauterine growth restriction fetuses: correlation with arterial blood gas analysis - Kaur, Triptpal; Bhatt, Reema Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Doppler is an ultrasound technique allowing non-invasive measurement of artery blood flow velocities. Objective of this study was to evaluate the role of umbilical artery (UA) and middle cerebral artery (MCA) Doppler study in predicting fetal hypoxia and acidosis in IUGR fetus and a population subjected to hematologic fluctuations. Methods: In this study 100 subjects with IUGR fetuses was evaluated for comparison of Doppler sonography analysis of fetal middle cerebral arteries and umbilical arteries and cord blood samples (pCO2, pO2) that was collected at the time of delivery. Results: Among the 100 subjects (between 28-32 gestational week) of IUGR showed a high risk of hypoxia and acidosis type condition. The observations were recorded in terms of MCA/UA ratio, the abnormal MCA/UA ratio was observed in significant (p<0.05) number of patients growth restricted fetuses (n=96), as compared to normal. There is a direct correlation found in the pH and pCO2 values. The results of arterial blood gases with respect to pH were found to be less than 7.3±1.6 in 96 subjects with abnormal MCA/UA ratio as compared to normal, that relates to the increase in the relative pCO2 (61.66%) [Acid increase] and decrease in pO2 arterial gases (Hpoxia increase). Conclusions: The study provides an insight that shows IUGR fetuses have a relatively higher risk of hypoxia (less oxygen) and acidosis (low pH and high pCO2), showed the most important determinants variations.